2008
DOI: 10.1152/ajplung.00316.2007
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory role for nucleosome assembly protein-1 in the proliferative and vasculogenic phenotype of pulmonary endothelium

Abstract: monary microvascular endothelial cells (PMVECs) are enriched with progenitor cells that underlie their rapid proliferation and vasculogenic capacity. However, the molecular basis for such an enhanced growth potential is unknown. Nucleosome assembly protein-1 (NAP1), and its related family of proteins, have been incriminated in control of cell growth in a range of species. We therefore sought to determine whether NAP1 contributes to the rapid proliferation and vasculogenesis that is observed in PMVECs. NAP1 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 32 publications
1
44
0
Order By: Relevance
“…A major difference between the studies demonstrating a role for TRPM2 and our current work is the location in the lung from which cells were derived. It is now widely recognized that there is regional heterogeneity within the pulmonary endothelium, and that LMVECs are phenotypically distinct from other cell types such as pulmonary conduit or systemic endothelial cells (11,14,21,51 (12), we used serum-free media during our ECIS experiments. Unfortunately, HC-067047 did not dissolve easily in our media buffer, resulting in the need to use a higher dose for the ECIS compared with [Ca 2ϩ ] i experiments.…”
Section: Discussionmentioning
confidence: 99%
“…A major difference between the studies demonstrating a role for TRPM2 and our current work is the location in the lung from which cells were derived. It is now widely recognized that there is regional heterogeneity within the pulmonary endothelium, and that LMVECs are phenotypically distinct from other cell types such as pulmonary conduit or systemic endothelial cells (11,14,21,51 (12), we used serum-free media during our ECIS experiments. Unfortunately, HC-067047 did not dissolve easily in our media buffer, resulting in the need to use a higher dose for the ECIS compared with [Ca 2ϩ ] i experiments.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure that the cells were capable of responding to VEGF, we confirmed the presence of phosphorylated VEGF receptor 2 and downstream ERK phosphorylation by Western blot, and we attenuated receptor phosphorylation using a tyrosine kinase inhibitor (data not shown). PAEC are isolated from proximal, conduit pulmonary arteries and are functionally distinct from PMVEC with respect to characteristics such as proliferative capacity and barrier function (9,33). To compare the migratory behavior of PAEC to that of PMVEC, we performed Boyden assays with a panel of agonists (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, two papers from Stevens and colleagues (2,9) have further highlighted the phenotypic and functional differences between microvascular and macrovascular lung EC. The authors identified a subpopulation of PMVEC (binding G. simplicifolia) that expressed classic EC antigens and progenitor cell markers.…”
Section: Discussionmentioning
confidence: 99%
“…PMVECs expressing PDE5A1 (2 ϫ 10 3 cells/well) and PAECs expressing siRNA-3 to inhibit PDE5 (5 ϫ 10 4 cells/well) were suspended in DMEM and seeded on Matrigel. For quantitative measurement of network formation, whole areas of each well were imaged, and the number of networks, composed of closed and continuous cords, was measured (2,8). The nuclear positions of angiogenic cells in the networks were imaged by UV fluorescent microscopy after methanol fixation and DAPI staining.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, microvascular endothelium appears to possess a greater angiogenic potential than does conduit endothelium; pulmonary microvascular endothelial cells (PMVECs) possess higher angiogenic capacity than do pulmonary artery endothelial cells (PAECs) (2,8). These two cell types also differ in the PDE isoforms they express, as PAECs express PDE5, whereas PMVECs do not express PDE5 and possess only trace levels of cGMP hydrolyzing activity (39).…”
mentioning
confidence: 99%